2019
DOI: 10.4102/jef.v12i1.400
|View full text |Cite
|
Sign up to set email alerts
|

Share-based remuneration: Per-director disclosure practices of selected listed South African companies

Abstract: The Johannesburg Stock Exchange (JSE), the Companies Act of 2008 (the Act) and the third King Report on Corporate Governance (King III) require disclosure on the share-based remuneration of directors of listed South African companies on a per-director basis. Research purpose:The first objective was to determine the disclosure practices of JSE-listed companies relating to share-based remuneration on a per-director basis, to examine whether the disclosure practices comply with regulatory requirements and whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
1
4
1
Order By: Relevance
“…It is found that all these control variables have a significant impact on the level of ESG score. In line with prior literature, ESG disclosure is positively and significantly influenced by size (Shahab & Ye, 2018;Shakil et al, 2020;Steenkamp et al, 2019). More prominent companies have sufficient resources and facilities to provide more information on their activities related to ESG.…”
Section: Regression Analysissupporting
confidence: 82%
“…It is found that all these control variables have a significant impact on the level of ESG score. In line with prior literature, ESG disclosure is positively and significantly influenced by size (Shahab & Ye, 2018;Shakil et al, 2020;Steenkamp et al, 2019). More prominent companies have sufficient resources and facilities to provide more information on their activities related to ESG.…”
Section: Regression Analysissupporting
confidence: 82%
“…Similarly, our results demonstrate that the estimated coefficient of firm size is not significant in the first and third models, indicating this variable not affect CG and ethics disclosure by companies of our sample. Such a result contradicts the results of Cunha and Mendes (2016) and Steenkamp et al (2019). In the second model, the estimated coefficient of firm size is positive and significant at the level of 5 per cent, which is an indication that larger firms disclose more environmental-related information than smaller firms.…”
Section: Empirical Findings and Discussioncontrasting
confidence: 70%
“…As firm size was measured by the natural logarithm of total assets (Shahab and Ye, 2018; Ofoegbu et al , 2018), the majority of empirical studies has reported significant evidence that there is a positive relation between company size and the level of CG disclosure (Cunha and Mendes, 2016; Steenkamp et al , 2019) and social and environmental disclosure (Shahab and Ye, 2018); Welbeck et al , 2017)).…”
Section: Methodsmentioning
confidence: 99%
“…With excessive executive remuneration often paid to executives of poorly performing Long-term incentives, such as share options and performance shares, are increasingly applied in executive remuneration packages (Steenkamp & Wesson 2018) and the value realised from LTIs often exceeds the remuneration earned from guaranteed packages and other benefits (Massie, Collier & Crotty 2014). The recognition and disclosure rules pertaining to LTIs, however, lead to stakeholders generally only learning about the extent and nature of LTIs when they are realised (in cash or shares) (Steenkamp et al 2019). Owing to potentially large amounts spent on executive LTIs, it is important that executive LTIs are governed effectively (Steenkamp et al 2019).…”
Section: Introduction Settingmentioning
confidence: 99%
“…The recognition and disclosure rules pertaining to LTIs, however, lead to stakeholders generally only learning about the extent and nature of LTIs when they are realised (in cash or shares) (Steenkamp et al 2019). Owing to potentially large amounts spent on executive LTIs, it is important that executive LTIs are governed effectively (Steenkamp et al 2019). Governance includes the appropriate design of executive LTI packages and transparent disclosure on the link between company strategy and executive LTI scheme objectives.…”
Section: Introduction Settingmentioning
confidence: 99%